2020
DOI: 10.1111/dth.13384
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic considerations and clinical characteristics of a sample of adolescent patients with acne vulgaris in Tirana, Albania: A cross‐sectional study

Abstract: Acne vulgaris is a common adolescent disorder but the data related to acne vulgaris is insufficient in Albania. The aim of this study was to assess the epidemiologic features of acne vulgaris and to identify lifestyle and constitutional factors in formulating a proper management protocol. A cross‐sectional study conducted on a representative sample of 2036 adolescents from 10 high schools located in Tirana. A self‐administered questionnaire was administered to collect the data. The binary logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a Norwegian study conducted among adolescents showed that high intake of dairy products is significantly associated with moderate to severe acne ( 20 ). Other factors such as diet rich in free fatty acids and sugar which contributed to aggravation of acne ( 16 21 ). Fiber poor diet was consumed by the participants of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a Norwegian study conducted among adolescents showed that high intake of dairy products is significantly associated with moderate to severe acne ( 20 ). Other factors such as diet rich in free fatty acids and sugar which contributed to aggravation of acne ( 16 21 ). Fiber poor diet was consumed by the participants of our study.…”
Section: Discussionmentioning
confidence: 99%